Community Economic Empowerment in Sukamaju Village Through Strengthening Business Skills Ornamental Fish (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This article is resulting from community service activities (PKM) organized by the Faculty of Economics and Business, Widyatama University in collaboration with partners, namely the Family Welfare Improvement Effort (UP2K) PKK Sukamaju Village, Bandung City. The PKM activity carried out was training aimed at empowering the community's economy and/or businesses fostered by UP2K Sukamaju Village in the form of increasing the ability of ornamental fish businesses for export purposes. The stages of implementing the activities carried out consisted of 6 stages including (1) pre-survey, (2) proposal preparation, (3) preparation, (4) implementation, (5) monitoring and evaluation, and (6) preparation of activity reports. The participants in this training activity were 30 people. The training activities carried out were in the form of presentations of materials from resource persons accompanied by discussions or questions and answers as well as simulations or demos. The results are also the main conclusions of the PKM activities carried out, namely that ornamental fish cultivation and export business is a promising business for residents or businesses fostered by UP2K Sukamaju Village. The initial stage of starting a business for participants after training is the cultivation of Brushmouth Black Slayer fish, Brushmouth Albino Slayer, and Corydoras and improving several competitive strategies for old entrepreneurs. Some suggestions for similar PKM activities or future developments include providing initial business capital and presenting international speakers or participants.